Improved switching table for direct power control of three-phase PWM rectifier - Baktash, A.; Vahedi, A.; Masoum, Mohammad (Curtin University of Technology, 2007)
The switching table based direct power control (ST-DPC) of three-phase PWM rectifier is analysed and an improved switching table (IST-DPC) is presented. The proposed switching schedule improves the quality of line current and results in better dynamic performances. In addition, the predictive direct power control (PDPC) of three-phase boost rectifier is presented and simulation results (in MATLAB/SIMULINK environment) are compared with those generated by ST-DPC and ISD-DPC approaches. Advantages and limitations of each control scheme are highlighted and conclusions regarding applications, quality of current waveforms and burden of calculations are presented.